Analysis of motor activities of professional soccer players - Andrzejewski, M.; Chmura, J.; Pluta, B.; Kasprzak, A. (The Journal of Strength and Conditioning Research, 2012)
The objective of this study was to determine the distance covered by professional soccer players during matches with the use of the computerized match analysis system Amisco Pro® (version 1.0.2, Nice, France). Kinematic examination included the specification of the distance covered by 31 players participating in 4 matches in the Union of European Football Association Cup competitions during the 2008-2009 season. Data were analyzed based on players' positions on the pitch, changes in the players' motor activity intensity level, and match period (first or second half). The results of statistical analysis revealed that the average total distance covered by all players (n = 31) was 11,288 ± 734 m. With respect to the player's position on the pitch, the midfielders traveled the longest average distance (11,770 ± 554 m) during the game. This was 3% longer than the distance achieved by the attackers at 11,377 ± 584 m, and 7% longer than that achieved by the defenders 10,932 ± 728 m. The analysis of physical loads on soccer players during a match is highly useful for training individualization. It provides a tool for effective planning and for recording the loads on players, which is an indispensable element of modern coaching.